Evaluation of Flexure Strength of Heat Cure Acrylic Resin Reinforcement with Nano Al2O3 After Polishing with Different Abrasive Materials - Nihad AlFuraiji; Wafaa Atallah; Syed Saad B Qasim (Journal of Techniques)
Composites with Nano fillers reinforced by polymer structures are gaining popularity in the field of prosthodontic. Composite materials are being developed to meet the needs of patients, such as heat cure acrylic resins, that used so much in the field of prosthodontic.